Structural Proteins of Bovine Coronavirus and Their Intracellular Processing - Deregt, Dirk; Sabara, Marta; Babiuk, Lorne A. (Journal of General Virology, 1987)
Summary The Quebec isolate of bovine coronavirus (BCV) was found to contain four unique major structural proteins. These proteins consisted of the peplomeric protein (gp190/E2, gp100/E2), the nucleocapsid protein (p53/N) and its apparent trimer (p160/N), a family of small matrix glycoproteins (gp26/El, gp25/El and p23/El) and the putative haemagglutinin (gpl24/E3). Pulse-chase experiments utilizing polyclonal antiserum and monoclonal antibodies indicated that the unique BCV E3 protein had as its primary precursor an A-linked glycoprotein with an M r of 59000 (gp59) which underwent rapid dimerization by disulphide bond formation to yield gp118. Further glycosylation of gp118 produced gp124/E3 which incorporated fucose. Thus gp124/E3 was probably a homodimer. The processing of the E2 and E1 proteins of BCV was similar to that shown previously for mouse hepatitis virus. A large AM inked precursor glycoprotein, gpl70, underwent further glycosylation to yield gp190/E2 before subsequent proteolytic cleavage to yield gp100/E2. The glycosylated El (gp26, gp25) proteins arose as a result of O-linked glycosylation of p23/El as indicated by the resistance of these species to tunicamycin.
Keywords: glycoprotein processing